Costo efectividad en el diagnóstico de esguince de tobillo, basado en los criterios de Ottawa, periodo 2014 al 2015 en el hospital Manuel Ygnacio Monteros de Loja - Alvarez Jimenez, Steven Santiago (2018)
Abstract:In order to analyze the applicability of the Ottawa rules as clinical measures in the management of acute traumatic ankle injuries in the Manuel Ygnacio Monteros de Loja Hospital during the 2014-2015 period, the present study was carried out with a quantitative approach, descriptive type - transversal, retrospective A sample of 46 patients was studied, taking into account inclusion and exclusion criteria. It was identified: - patients to whom the Ottawa ankle rules were applied. - patients who were asked for foot and / or ankle radiographs - cost of x-rays, stay in the emergency unit, the results were compared with other studies related to the subject through which it was evidenced that: There was no application of the ankle rules of Ottawa, the main diagnostic method was AP and lateral radiography, the cost of radiological studies during the two years was $ 544.30, while those of stay in the emergency room it was $ 382.66 giving a total cost sum of $ 926.58.